1991
DOI: 10.1021/bi00232a036
|View full text |Cite
|
Sign up to set email alerts
|

Expression of spinach glycolate oxidase in Saccharomyces cerevisiae: purification and characterization

Abstract: Glycolate oxidase from spinach has been expressed in Saccharomyces cerevisiae. The active enzyme was purified to near-homogeneity (purification factor approximately 1400-fold) by means of hydroxyapatite and anion-exchange chromatography. The purified glycolate oxidase is nonfluorescent and has absorbance peaks at 448 (epsilon = 9200 M-1 cm-1) and 346 nm in 0.1 M phosphate buffer, pH 8.3. The large bathochromic shift of the near-UV band indicates that the N(3) position is deprotonated at pH 8.3. A pH titration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
82
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 36 publications
14
82
1
Order By: Relevance
“…Under the same experimental conditions, the amounts of products generated from palmitic acid and palmitoleic acid by the A264E mutant were ϳ30 -40% lower than those produced by wild-type P450 BM3, consistent with the differences in steady-state kinetics shown in Table I. In parallel studies of peroxide production during fatty acid turnover, there was no significant difference between the wild-type and A264E enzymes, suggesting that both enzymes couple NADPH oxidation to fatty acid oxygenation tightly, but that the A264E mutant is a much slower hydroxylase than wild-type P450 BM3 (44). Thus, despite the unusual spectral conversions produced upon binding longchain fatty acids, the A264E flavocytochrome retains the capacity to oxygenate fatty acids.…”
Section: Resultssupporting
confidence: 76%
“…Under the same experimental conditions, the amounts of products generated from palmitic acid and palmitoleic acid by the A264E mutant were ϳ30 -40% lower than those produced by wild-type P450 BM3, consistent with the differences in steady-state kinetics shown in Table I. In parallel studies of peroxide production during fatty acid turnover, there was no significant difference between the wild-type and A264E enzymes, suggesting that both enzymes couple NADPH oxidation to fatty acid oxygenation tightly, but that the A264E mutant is a much slower hydroxylase than wild-type P450 BM3 (44). Thus, despite the unusual spectral conversions produced upon binding longchain fatty acids, the A264E flavocytochrome retains the capacity to oxygenate fatty acids.…”
Section: Resultssupporting
confidence: 76%
“…In a recent study of wild-type glycolate oxidase, it was confirmed that this enzyme exhibits all these features and can be regarded as a typical member of this class of flavoproteins (Macheroux et al, 1991). Moreover it was found that all its properties in solution are compatible with the X-ray crystal structure.…”
mentioning
confidence: 69%
“…The mutant was identified by dideoxynucleotide sequencing. After cloning the mutant gene into the EcoRI restriction site of expression vector pGAO (Macheroux et al, 1991), the orientation was determined with an asymmetric EcoRV digest and the mutation was verified by dideoxy sequencing. Introduction of the Y129F mutation into the Escherichiu coli expression plasmid (pPM1, see Macheroux et al, 1992) was achieved by exchanging the NsiI-Sac1 fragment of the the wild-type glycolate oxidase gene with the fragment containing the Y129F mutation.…”
Section: Oligonucleotide-directed Mutagenesismentioning
confidence: 99%
See 2 more Smart Citations